Service Innovation in Agricultural Business Exploring the Influence of Digital Information Technologies - Gack, Sebastian (BestMasters,, 2018)
This thesis provides a holistic view on the topic via an exploratory interview study approach. Looking through a service-dominant-logic-lens, the author puts the insights of the farm automatization industry in relation to existing service innovation literature. The influence of interconnectivity is illustrated stepwise. Models of the present and the future value network are drawn, which show the expanding need of information exchange between the value network and the supply chain. Additionally, the author identifies the interplay of interconnectivity and the demand for transparency as the driver for new service innovations. To ensure the information exchange, the need of a non-proprietary data exchange platform in the agricultural sector is being suggested. Content Service Innovation Impact of digitalization and interconnectivity on service innovation Product-service-systems and value networks Service-dominant-logic Data collection and analysis Managerial implications for theory and management Target Groups Lecturers and students in the areas of product/service and business development and sales Practitioners in product/service innovation and business development and sales The Author Sebastian Gack obtained a Master of Science (M.Sc.) in industrial engineering & management and a Master of Science (M.Sc.) in mechanical engineering at Friedrich-Alexander-University in Erlangen-Nuremberg. During his years abroad at the University Polytechnique Montreal and Rennes 1 he increased his experience in service and product development. .